Thymoquinone Prevents Dopaminergic Neurodegeneration by Attenuating Oxidative Stress Via the Nrf2/ARE Pathway - Dong, Jianjian; Zhang, Xiaoming; Wang, Shijing; Xu, Chenchen; Gao, Manli; Liu, Songyang; Li, Xiaoxiao; Cheng, Nan; Han, Yongsheng; Wang, Xun; Han, Yongzhu (Frontiers in Pharmacology, 2021)
Studies have indicated that oxidative stress plays a crucial role in the development of Parkinson’s disease (PD) and other neurodegenerative conditions. Research has also revealed that nuclear factor erythroid 2-related factor 2 (Nrf2) triggers the expression of antioxidant genes via a series of antioxidant response elements (AREs), thus preventing oxidative stress. Thymoquinone (TQ) is the bioactive component of Nigella sativa, a medicinal plant that exhibits antioxidant and neuroprotective effects. In the present study we examined whether TQ alleviates in vivo and in vitro neurodegeneration induced by 1-methyl-4-phenylpyridinium (MPP+) and 1-methyl-4-phenyl-1,2,3,6-tetrahydropyridine (MPTP) by acting as an activator of the Nrf2/ARE cascade. We showed that TQ significantly reduced MPP+-mediated cell death and apoptosis. Moreover, TQ significantly elevated the nuclear translocation of Nrf2 and significantly increased the subsequent expression of antioxidative genes such as Heme oxygenase 1 (HO-1), quinone oxidoreductase (NQO1) and Glutathione-S-Transferase (GST). The application of siRNA to silence Nrf2 led to an abolishment in the protective effects of TQ. We also found that the intraperitoneal injection of TQ into a rodent model of PD ameliorated oxidative stress and effectively mitigated nigrostriatal dopaminergic degeneration by activating the Nrf2-ARE pathway. However, these effects were inhibited by the injection of a lentivirus wrapped Nrf2 siRNA (siNrf2). Collectively, these findings suggest that TQ alleviates progressive dopaminergic neuropathology by activating the Nrf2/ARE signaling cascade and by attenuating oxidative stress, thus demonstrating that TQ is a potential novel drug candidate for the treatment of PD.